FLIPPED CLASSROOM METHOD ON TEACHING AND LEARNING OF BIOLOGY IN SECONDARY SCHOOL (NAU Journal of Technology and Vocational Education, 2026)
Effective teaching and learning cannot be accomplished without proper management of the learning process. The need to change classroom orientation from teacher – centred to student – centred for more active involvement as a way of improving students’ learning is well recognised. From this research, flipped classroom make teaching and learning enjoyable, productive, engaging, effective, and satisfying. In addition, flipped classroom is a powerful tool used to achieve academic, behavioural and affective goals. Efficient use of flipped classroom will increase students’ attitude that reflects the engagement of students and improves their performance. Teachers should adopt the flipped classroom approach because it is a student-centred learning strategy that involves the students rather than spoon-feeds them. It was recommended that; teachers should seek for more knowledge on the utilisation of flipped classroom for instruction, stakeholders in the education industry should appreciate, support and sustain the use of flipped classroom, government should, supply adequate technological facilities that will sustain flipped classroom integration in all secondary schools in Ekiti State, and school management should allocate both finance and resources to promote professional development of teachers.
Keywords: Flipped classroom; Teaching; Learning; Biology; Secondary School